A socio-technical analysis of internet of things development: an interplay of technologies, tasks, structures and actors. Issue 6 (28th August 2019) - Ghaffari, Kimia; Lagzian, Mohammad; Kazemi, Mostafa; Malekzadeh, Gholamreza
Abstract : Purpose: Prior research on the area of internet of things (IoT) development has primarily emphasized the overview descriptions and rarely investigated this area from a socio-technical standpoint. However, IoT development is a socio-technical ensemble, which requires analysis with a simultaneous focus on both technical and non-technical issues. Hence, this paper aims to analyze the development of IoT through the lens of the socio-technical system (STS) theory. Design/methodology/approach: Having reviewed the STS theory, the key components of the IoT development are identified using prior literature review and semi-structured interviews with experts involved in the Iranian IoT development effort. Findings: As a result, this paper provides insight into the key socio-technical issues in the IoT development classified under technology, tasks, structure and actors as four components of STS. Moreover, the close connections between the components are clarified. Originality/value: This research is among the earliest studies, which use the STS theory to investigate the IoT development. The conducted socio-technical analysis of this study may assist the governments, industries and entrepreneurs as the chief stakeholders of IoT development to better align their actions with each other and achieve a balance between both technical and social sides.